“MLK's functional philosophy of non-violence” - Mann, Jeffrey K. (Dialog, 2024)
The fact that Martin Luther King, Jr. held a moral philosophy of non-violence is well known. What is less familiar is that he made various exceptions to his prohibitions on violence. Given the absolute language he often used in condemning violent acts, he can give the impression of inconsistency in his ethics. The reality, however, is that his moral framework possesses both consistency and functionality. That is, it holds together logically and has practical usefulness. The key to understanding King is to view his moral philosophy through the lens of Virtue Ethics, not rule-based ethics. This approach to a philosophy of non-violence provides value and utility to adherents of both pacifism and Just War Theory, a difficult feat.